Pengaruh Penerapan Belajar Dari Rumah Terhadap Motivasi Belajar Siswa SDN Serdang Wetan - Gusita, Devi; Rosyid, Ainur (Didaktika, 2021)
This study aims to examine whether the application of learning from home affects students' learning motivation. The research method uses a survey method with a quantitative approach and the research instrument uses a questionnaire with a Likert scale of 5 answer choices. The population in this study were all upper-level class students of Serdang Wetan State Elementary School in Legok District, Tangerang Regency, Banten. The sample of this study consisted of 30 students who were randomly selected from 3 classes, the sampling was determined by probability sampling technique with the type of simple random sampling. The results showed that (1) the implementation of learning activities from home has a implementation percentage value of 69.43% which is categorized as good enough; (2) student motivation in learning and participating in learning carried out from home has a percentage value of 79.11% which is categorized as good enough. The implication of this research is that good student self-motivation can certainly encourage learning motivation to carry out learning carried out from home.Â